Systemic Lupus Erythematosus and Rapid Progressive Glomerulonephritis with History of Hypothyroidism: A Case Report - Adolf Gideon; Ni Wayan Sri Wardani; Dewa Wedha Asmara (Riviera Publishing, 2025)
A 20 years old female presented to the ER with fever and multiple joint pain, especially in hands and feet. Patient also have dry cough without blood, and weight loss in the last few months. There were no other symptoms. Patient had a medical history of hypothyroidism with episodic thyroid enlargement since 2022. Medications were irregularly taken, and there was a relapse in 2023. After a few days of treatment. After a few days of treatment, new symptomps such as hemoptysis, dyspnea, high-grade fever and chills emerged. This was followed by vomiting, bloating, and difficulty in defecation. Laboratory examination revealed hypothyroidism, anemia, and thrombocytopenia with decreased kidney function. Complete urine test showed blood (hematuria) and protein (proteinuria) in urine. Chest X Ray indicated cardiomegaly and pneumonia with mild effusion. Subsequently, we suspected Systemic Lupus Erythematosus (SLE), and Rapid Progressive Glomerulonephritis, with confirmed diagnoses of hypothyroidism and pneumonia. ANA IF (for SLE), abdominal ultrasonography, and viral examination were performed to confirm our diagnosis. Several days later, ANA IF results returned significantly positive, confirming the diagnosis of SLE based on the ACR/EULAR 2019 criteria. This report underscores the importance of history-taking, physical examination and laboratory examination in suspected cases of systemic lupus erythematosus. Early recognition and appropriate management are crucial in achieving favorable outcomes for the patients.